A novel cohesive zone model for predicting the interface bonding behaviours of the ballastless track of high-speed railway. (July 2022) - Lu, Zhao-Hui; Wang, Jun; Tang, Zhuo; Zhao, Yan-Gang; Li, Wengui
Abstract: The interface damage is one of the main concerns for high-speed railway ballastless track structures during its whole service life, as it would affect the reliability of track structures or even cause the high-speed train accident. In this paper, various existing cohesive zone models (CZMs) were identified and compared regarding the performance in modeling the interface behaviors of ballastless track structures. The results show that the existing CZMs cannot accurately represent the nonlinear relationship of the ascending and descending sections in the interface traction-separation curve concurrently. Therefore, a new CZM was proposed in this study, and the feasibility of the proposed model was examined by the experimental results. It indicates that the proposed model can reasonably describe the nonlinear behaviors of the ascending and descending sections in the traction-separation curve by introducing exponential coefficients. The proposed CZM also exhibits higher accuracy in predicting the normal and tangential cracking behaviors of the interlayer interface of the ballastless track structures in comparison with the existing models, with the coefficients of determination ( R 2 ) in the fitting results all above 0.85. As a result, this model can be used for the analysis of the interface behaviours of ballastless track structures.